TRI HITA KARANA CULTURE AS A MODERATION AND ITS INFLUENCE ON THE FINANCIAL PERFORMANCE OF VILLAGE CREDIT INSTITUTIONS - I Gusti Ayu Ratih Permata Dewi (Universitas PGRI Madiun, 2023)
ABSTRACTThe purpose of this study is to ascertain the relationship between CSR and GCG and financial performance, as well as how Tri Hita Karana influences that relationship in the Tabanan District for LPDs. The study's population comprised one hundred four people who worked for 10 LPDs in the Tabanan district. Purposive sampling was utilized as the sampling technique, and up to 64 individuals met the criteria and served as samples. PLS was employed in the data analysis process. The findings demonstrate that CSR has a favorable and considerable impact on financial performance. GCG positively and significantly impacts Financial Performance. Tri Hita Karana positively and significantly influences Financial Performance. Tri Hita Karana can limit how much CSR affects financial performance. Tri Hita Karana can temper the impact of GCG on financial performance.ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh CSR dan GCG terhadap Kinerja Keuangan serta untuk mengetahui Tri Hita Karana dalam memoderasi pengaruh CSR dan GCG terhadap Kinerja Keuangan LPD se-kecamatan Tabanan. Populasi di dalam penelitian ini adalah orang karyawan dari 10 LPD se-kecamatan Tabanan yang berjumlah 104 orang. Teknik pengambilan sampel menggunakan purposive sampling dengan kriteria dan jumlah sampel yang dijadikan sampel sebanyak 64 orang. Teknik analisis data menggunakan PLS. Temuan menunjukkan bahwa CSR memiliki dampak yang menguntungkan dan cukup besar terhadap kinerja keuangan. GCG berpengaruh positif dan signifikan terhadap Kinerja Keuangan. Tri Hita Karana berpengaruh positif dan signifikan terhadap Kinerja Keuangan. Tri Hita Karana dapat membatasi seberapa besar pengaruh CSR terhadap kinerja keuangan. Tri Hita Karana dapat meredam dampak GCG terhadap kinerja keuangan.